Separator and non-aqueous electrolyte secondary battery including same

The separator design with a ceramic layer and angled adhesive stripe pattern addresses sticking and gas release issues, improving electrolyte impregnation and reducing battery resistance in non-aqueous electrolyte secondary batteries.

JP7611802B2Active Publication Date: 2025-01-10PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021184690
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-12
Publication Date
2025-01-10
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

The use of an adhesive resin on the surface of separators in non-aqueous electrolyte secondary batteries leads to electrical charging, causing sticking issues, hindered gas release during winding, reduced porosity affecting electrolyte impregnation, and increased battery resistance.

Method used

A separator design featuring a porous resin base material with a ceramic layer containing 85% inorganic particles and an adhesive layer with a stripe pattern, incorporating inorganic particles and adhesive resin, angled at 20° to 70°, to enhance antistatic properties, gas release, and electrolyte impregnation.

Benefits of technology

The separator provides improved adhesion to electrodes, facilitates easy winding, enhances electrolyte impregnation, reduces battery resistance, and maintains production efficiency while preventing separator sticking and electrolyte discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611802000002
    Figure 0007611802000002
  • Figure 0007611802000003
    Figure 0007611802000003
  • Figure 0007611802000004
    Figure 0007611802000004
Patent Text Reader

Abstract

To provide a separator which is excellent in antistatic properties, degassing capability in winding, and impregnation property of a non-aqueous electrolyte in formation of an electrode body.SOLUTION: A separator has a base material layer made of a porous resin, and a ceramic layer containing 85 mass% or more of first inorganic particles on at least one surface thereof. The main surface of the separator has long sides. The separator further has an adhesive layer provided on at least the one main surface thereof at a predetermined pitch so as to form a stripe pattern. The adhesive layer contains an adhesive resin, and second inorganic particles. A content of the second inorganic particles in the adhesive layer is 3 mass% or more and 65 mass% or less. An angle between the adhesive layer and the long sides of the main surface of the separator is 20° or more and 70° or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator. The present invention also relates to a nonaqueous electrolyte secondary battery including the separator. [Background technology]

[0002] 2. Description of the Related Art In recent years, nonaqueous electrolyte secondary batteries such as lithium ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.

[0003] In non-aqueous electrolyte secondary batteries, a separator is used to insulate the positive electrode from the negative electrode. A separator in which a porous resin substrate and a ceramic layer containing inorganic particles are laminated is known. In addition, a technique is known in which an adhesive resin is disposed on the surface of the separator to improve the adhesion between the electrode and the separator (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5572101 Specification Summary of the Invention [Problem to be solved by the invention]

[0005] However, as a result of intensive research by the present inventors, it was found that when an adhesive resin is disposed on the surface of a separator, the adhesive resin becomes charged, which causes problems during the manufacture of the separator, such as the separators sticking to each other, the winding core not being able to be removed, and defects caused by discharge. It was also found that problems such as the separator being prevented from escaping during winding, making it difficult to wind smoothly, and the handleability of the wound body being reduced. Furthermore, it was found that when a separator and an electrode are bonded to form an electrode body, the porosity of the separator is reduced, which reduces the impregnation of the nonaqueous electrolyte, which may adversely affect the resistance characteristics of the battery.

[0006] Therefore, an object of the present invention is to provide a separator that is excellent in antistatic properties, gas release properties during winding, and impregnation properties with a non-aqueous electrolyte during formation of an electrode assembly. [Means for solving the problem]

[0007] The separator disclosed herein comprises a substrate layer made of a porous resin, and a ceramic layer containing 85% or more by mass of first inorganic particles on at least one surface of the substrate layer. The separator has a main surface with a long side. The separator further comprises an adhesive layer provided on at least one of the main surfaces at a predetermined pitch so as to form a stripe pattern. The adhesive layer contains an adhesive resin and second inorganic particles. The content of the second inorganic particles in the adhesive layer is 3% by mass or more and 65% by mass or less. The angle between the adhesive layer and the long side of the main surface of the separator is 20° or more and 70° or less.

[0008] According to this configuration, it is possible to provide a separator that is excellent in antistatic properties, gas release properties during winding, and impregnation properties with a nonaqueous electrolyte solution during formation of the electrode assembly.

[0009] In a preferred embodiment of the separator disclosed herein, the angle between the adhesive layer and the long side of the main surface of the separator is 45° to 60°. With this configuration, a separator with higher impregnation ability with a nonaqueous electrolyte can be provided.

[0010] In a preferred embodiment of the separator disclosed herein, the adhesive resin is polyvinylidene fluoride, which provides the separator with particularly high adhesion to the electrodes and prevents the adhesive resin from adversely affecting the battery characteristics.

[0011] In a preferred embodiment of the separator disclosed herein, the second inorganic particles contained in the adhesive layer are alumina, boehmite, magnesia, or barium sulfate particles. This configuration can prevent the second inorganic particles from adversely affecting the battery characteristics, and these particles are inexpensive and therefore excellent in terms of cost.

[0012] In a preferred embodiment of the separator disclosed herein, the adhesive layer has a width of 0.5 mm to 4 mm, and the adhesive layer covers 50% to 90% of the main surface of the separator. With this configuration, a separator with particularly high impregnation ability for a non-aqueous electrolyte can be provided.

[0013] From another aspect, the present disclosure provides a nonaqueous electrolyte secondary battery comprising an electrode assembly including a positive electrode, a negative electrode, and a separator insulating the positive electrode and the negative electrode, and a nonaqueous electrolyte. The separator is the separator described above. With this configuration, a nonaqueous electrolyte secondary battery with excellent production efficiency can be provided. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic diagram (top view) of a separator according to one embodiment of the present invention, viewed from a direction perpendicular to a main surface thereof. [Diagram 2] FIG. 2 is a partial cross-sectional view that illustrates a separator according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a partially enlarged view of the vicinity of the long side of FIG. [Figure 4] 1 is a cross-sectional view showing a schematic internal structure of a lithium-ion secondary battery including a separator according to one embodiment of the present invention. [Diagram 5] 4 is a schematic exploded view showing the configuration of a wound electrode body of a lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described by using the same reference numerals. In addition, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships.

[0016] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged, and includes so-called storage batteries and electricity storage elements such as electric double layer capacitors. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0017] A separator according to the present embodiment, as one example of the separator disclosed herein, is illustrated in Fig. 1 to Fig. 3. Fig. 1 is a schematic diagram (top view) of the separator according to the present embodiment as viewed from a direction perpendicular to the main surface. Fig. 2 is a partial cross-sectional view of the separator according to the present embodiment. Fig. 3 is a partial enlarged view of the vicinity of the long side of Fig. 1.

[0018] As shown in Fig. 2, the separator 70 according to this embodiment includes a substrate layer 72 made of a porous resin and a ceramic layer 74 containing first inorganic particles. In Fig. 1, the MD direction indicated by the arrow is the longitudinal direction of the separator 70, and as shown in Fig. 1, the main surface of the separator 70 has a long side parallel to the MD direction. In the illustrated example, the separator 70 is elongated so that it can be easily manufactured continuously. However, the separator 70 does not have to be elongated as long as the main surface has a long side.

[0019] The porous resin constituting the substrate layer 72 may be a known porous resin used in separators for non-aqueous electrolyte secondary batteries. Examples of the resin include polyolefin, polyester, cellulose, polyamide, etc. Among them, polyolefin is preferable because it can impart a so-called shutdown function to the separator 70. Examples of suitable polyolefin include polyethylene (PE) and polypropylene (PP).

[0020] The base layer 72 may have a single layer structure, or may have a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer).

[0021] The thickness of the base layer 72 is not particularly limited as long as it can insulate the positive and negative electrodes, and is, for example, from 8 μm to 40 μm, preferably from 10 μm to 25 μm, and more preferably from 10 μm to 14 μm.

[0022] The porosity of the substrate layer 72 is not particularly limited and may be the same as the porosity of known substrate layers of separators for non-aqueous electrolyte secondary batteries. The porosity of the substrate layer 72 is, for example, 20% to 70%, preferably 30% to 60%, and more preferably 40% to 50%. The porosity of the substrate layer 72 can be measured by mercury intrusion porosimetry.

[0023] The air permeability of the substrate layer 72 is not particularly limited and may be the same as the porosity of a known substrate layer of a separator for a nonaqueous electrolyte secondary battery. The air permeability of the substrate layer 72 is, for example, 50 sec / 100 mL or more and 600 sec / 100 mL or less, preferably 150 sec / 100 mL or more and 300 sec / 100 mL or less, in terms of Gurley value. The Gurley value of the substrate layer 72 can be measured by a method specified in JIS P8117 (2009).

[0024] The type of the first inorganic particles contained in the ceramic layer 74 is not particularly limited. Examples of the first inorganic particles include oxide ceramic particles such as alumina (Al2O3), silica (SiO2), titania (TiO2), zirconia (ZrO2), magnesia (MgO), ceria (CeO2), and zinc oxide (ZnO); nitride ceramic particles such as silicon nitride, titanium nitride, and boron nitride; metal hydroxide particles such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide; clay mineral particles such as mica, talc, boehmite, zeolite, apatite, and kaolin; sulfate particles such as barium sulfate and strontium sulfate; and glass fibers. Among them, alumina and boehmite particles are preferably used. Alumina and boehmite have a high melting point and excellent heat resistance. In addition, alumina and boehmite have a relatively high Mohs hardness and are also excellent in mechanical strength and durability. Furthermore, alumina and boehmite are relatively inexpensive. Raw material costs can be reduced.

[0025] The shape of the first inorganic particles is not particularly limited, and may be spherical or non-spherical. The average particle diameter (D50) of the first inorganic particles is not particularly limited, and is, for example, 0.1 μm to 5 μm, preferably 0.3 μm to 3 μm, and more preferably 0.5 μm to 1.5 μm. In this specification, the average particle diameter (D50) refers to the median diameter (D50), and therefore means the particle diameter corresponding to a cumulative frequency of 50 volume % from the fine particle side with a small particle diameter in the volume-based particle size distribution based on the laser diffraction / scattering method. Therefore, the average particle diameter (D50) can be obtained using a known laser diffraction / scattering type particle size distribution measuring device or the like.

[0026] The ceramic layer 74 may contain components other than the first inorganic particles, examples of which include a binder, a thickener, etc. Examples of the binder include fluorine-based polymers such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), acrylic binders, rubber-based binders such as styrene butadiene rubber (SBR), polyolefin-based binders, etc. Examples of the thickener include carboxymethyl cellulose (CMC), methyl cellulose (MC), etc.

[0027] The content of the first inorganic particles in the ceramic layer 74 is 85% by mass or more. By having the content of the first inorganic particles be 85% by mass or more, high strength and heat resistance can be imparted to the ceramic layer 74. The content of the first inorganic particles in the ceramic layer 74 is preferably 90% by mass or more and 97% by mass or less, and more preferably 92% by mass or more and 97% by mass or less.

[0028] The content of the binder in the ceramic layer 74 is 15 mass % or less, preferably 3 mass % to 10 mass %, and more preferably 3 mass % to 8 mass %.

[0029] The thickness of the ceramic layer 74 is not particularly limited, and is, for example, 0.3 μm or more and 6.0 μm or less, preferably 0.5 μm or more and 4.5 μm or less, and more preferably 1.0 μm or more and 2.0 μm or less.

[0030] The porosity of the ceramic layer 74 is not particularly limited and may be the same as that of known ceramic layers 74 in separators for non-aqueous electrolyte secondary batteries. The porosity of the ceramic layer 74 is, for example, 30% or more and 90% or less, preferably 40% or more and 80% or less, and more preferably 50% or more and 70% or less. The porosity of the ceramic layer 74 can be measured by mercury intrusion porosimetry.

[0031] In the illustrated example, the separator 70 has the ceramic layer 74 on only one main surface of the base layer 72. However, the separator 70 may have the ceramic layer 74 on both main surfaces of the base layer 72.

[0032] The separator 70 according to this embodiment further includes an adhesive layer 76. Thus, the separator 70 has a configuration in which the adhesive layer 76 is provided to the laminate of the substrate layer 72 and the ceramic layer 74.

[0033] In the illustrated example, the separator 70 has a main surface on the substrate layer 72 side and a main surface on the ceramic layer 74 side. The adhesive layer 76 is provided on at least one of the main surfaces of the separator 70. In the example shown in Fig. 2, the separator 70 has the adhesive layer 76 on both of its main surfaces (i.e., the main surface on the substrate layer 72 side and the main surface on the ceramic layer 74 side). However, the separator 70 may have the adhesive layer 76 only on the main surface on the substrate layer 72 side, or may have the adhesive layer 76 only on the main surface on the ceramic layer 74 side.

[0034] In this embodiment, the adhesive layer 76 is provided at a predetermined pitch so as to form a stripe pattern. Therefore, as shown in the figure, the adhesive layer 76 is formed as a convex portion extending in one direction. Therefore, on the main surface of the separator 70 on which the adhesive layer 76 is provided, regions having the adhesive layer 76 and regions without the adhesive layer 76 are alternately formed. Note that, due to technical limitations in manufacturing, it is permissible for a small amount of adhesive components to be attached to the regions without the adhesive layer 76 (for example, the coverage rate of the components of the adhesive layer 76 in the regions without the adhesive layer 76 is 5% or less, preferably 1% or less).

[0035] In this embodiment, the stripe pattern by the adhesive layer 76 is formed as an oblique stripe pattern. The angle between the adhesive layer 76 and the long side of the main surface of the separator 70 (i.e., the angle θ shown in FIG. 3) is 20° or more and 70° or less. Therefore, the adhesive layer 76 is inclined in the range of 20° or more and 70° or less with respect to the longitudinal direction of the separator 70 (the direction of the arrow MD in FIG. 1). The angle between the adhesive layer 76 and the long side of the main surface of the separator 70 may be an acute angle or an obtuse angle, but in this specification, the acute angle is adopted.

[0036] The adhesive layer 76 formed in such an oblique stripe pattern provides the separator 70 with excellent adhesion to the electrodes and excellent impregnation with the nonaqueous electrolyte. That is, the adhesive layer 76 is formed in a stripe pattern, so that a flow path for the nonaqueous electrolyte is formed between adjacent adhesive layers 76, and the nonaqueous electrolyte can easily permeate into the separator 70 in the region between the adjacent adhesive layers 76 (i.e., the region on the main surface of the separator 70 where the adhesive layer 76 is not present). At this time, the stripe pattern of the adhesive layer 76 is moderately inclined, so that the nonaqueous electrolyte can more easily impregnate the separator.

[0037] Therefore, if the angle θ between the adhesive layer 76 and the long side of the main surface of the separator 70 is out of the range of 20° to 70°, the impregnation with the nonaqueous electrolyte becomes insufficient. From the viewpoint of higher impregnation with the nonaqueous electrolyte, the angle θ is preferably 30° to 65°, and more preferably 45° to 60°.

[0038] When such a separator 70 having high non-aqueous electrolyte impregnation property is used in a non-aqueous electrolyte secondary battery, the battery resistance can be reduced.

[0039] In addition, when such separator 70 having high impregnation ability for nonaqueous electrolyte is used in a nonaqueous electrolyte secondary battery, the time required for impregnating the electrode body including separator 70 with the nonaqueous electrolyte during production can be shortened, thereby improving the production efficiency of the nonaqueous electrolyte secondary battery.

[0040] Furthermore, when the nonaqueous electrolyte secondary battery is repeatedly charged and discharged, the nonaqueous electrolyte is discharged from the electrode assembly due to the expansion of the active material used in the electrodes, but the discharged nonaqueous electrolyte is easily returned to the electrode assembly, so that an increase in the resistance of the nonaqueous electrolyte secondary battery when repeatedly charged and discharged can be suppressed.

[0041] Here, between the base material layer 72 and the ceramic layer 74 of the separator 70, the ceramic layer 74 has higher permeability to the nonaqueous electrolyte. Therefore, when the adhesive layer 76 is provided at least on the main surface of the base material layer 72, which has low permeability to the nonaqueous electrolyte, the adhesive layer 76 can more effectively improve the impregnation of the nonaqueous electrolyte.

[0042] Furthermore, since the adhesive layer 76 is formed continuously in one direction, the adhesiveness to the electrodes is higher than in the conventional technology in which the adhesive layer is arranged in a dot pattern.

[0043] On the main surface of separator 70 on which adhesive layer 76 is formed, the coverage ratio of the main surface of separator 70 with adhesive layer 76 (in other words, the coating area of ​​adhesive layer 76 on the main surface of separator 70) is not particularly limited. From the viewpoint of higher adhesion, the coverage ratio is preferably 50% or more, and more preferably 60% or more. On the other hand, from the viewpoint of particularly high impregnation of nonaqueous electrolyte and particularly low battery resistance, the coverage ratio is preferably 90% or less, and more preferably 80% or less.

[0044] The width of adhesive layer 76 (i.e., the dimension perpendicular to the extension direction of adhesive layer 76; dimension W shown in FIG. 3) is not particularly limited, but is, for example, 0.5 mm or more and 4 mm or less, and preferably 3 mm or more and 4 mm or less.

[0045] The distance between adhesive layers 76 (i.e., the width of the gap between adhesive layers 76; dimension P shown in FIG. 3) is not particularly limited, but is, for example, 0.5 mm or more and 4 mm or less, and preferably 0.5 mm or more and 2 mm or less.

[0046] The thickness of the adhesive layer 76 (i.e., the dimension in the direction perpendicular to the main surface of the separator 70) is not particularly limited and is, for example, 0.5 μm or more and 4.5 μm or less, preferably 0.5 μm or more and 2.5 μm or less, and more preferably 1.0 μm or more and 2.0 μm or less.

[0047] From the viewpoint of increasing the impregnation of the nonaqueous electrolyte by arranging the regions through which the nonaqueous electrolyte easily penetrates at a predetermined interval, it is preferable that the width of the adhesive layer 76 is 0.5 mm or more and 4 mm or less, and that the coverage rate of the main surface of the separator with the adhesive layer 76 is 50% or more and 90% or less.

[0048] 2, the adhesive layer 76 has a rectangular cross section. The rectangular cross section of the adhesive layer 76 makes it easy to obtain a large adhesive area with the electrode. However, the cross-sectional shape of the adhesive layer 76 is not limited thereto as long as it can bond the electrode and the separator 70.

[0049] The adhesive layer 76 contains an adhesive resin and second inorganic particles. By containing the second inorganic particles in the adhesive layer 76, the adhesive layer 76 can be made difficult to be charged, and in this case, by forming the adhesive layer 76 in a striped shape, the adhesive layer 76 has a particularly high antistatic property. Therefore, during the manufacture of the separator, problems such as unintended sticking of separators to each other, poor core removal, and defects caused by discharge due to charging of the adhesive layer 76 can be eliminated.

[0050] Furthermore, since the adhesive layer 76 contains the second inorganic particles and is formed in a striped pattern, the adhesive strength of the adhesive layer 76 is optimized, and the second inorganic particles impart unevenness to the surface of the adhesive layer 76. This makes it easier for gas (air) to escape when the separator 70 is wound up. In other words, this allows the separator 70 to have high gas escape properties. This makes it easier to wind up the separator 70, and also makes the wound separator 70 easier to handle.

[0051] The type of adhesive resin is not particularly limited as long as it can bond the electrodes and the separator 70. Examples of adhesive resins include polyvinylidene fluoride (PVDF); diene rubbers such as styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), and acrylonitrile-butadiene-styrene rubber (NSBR); (meth)acrylic resins such as polyacrylic acid, butyl acrylate-ethylhexyl acrylate copolymer, and methyl methacrylate-ethylhexyl acrylate copolymer; cellulose derivatives such as carboxymethyl cellulose and hydroxyalkyl cellulose; polyacrylonitrile; polyvinyl chloride; polyvinyl alcohol; polyvinyl butyral; and polyvinylpyrrolidone. The adhesive layer 76 may contain one of these adhesive resins alone or two or more of them. Among these, polyvinylidene fluoride is preferred from the viewpoints of high adhesion between the separator and the electrodes and prevention of adverse effects on the battery characteristics.

[0052] The adhesive resin content in the adhesive layer 76 is 35% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. On the other hand, the adhesive resin content is 97% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less.

[0053] The second inorganic particles may be the same as those exemplified as the first inorganic particles. The second inorganic particles are preferably alumina, boehmite, magnesia, and barium sulfate particles. These particles can prevent the second inorganic particles from adversely affecting the battery characteristics, and are inexpensive and therefore excellent in terms of cost. The second inorganic particles are more preferably alumina and boehmite particles. The first inorganic particles contained in the ceramic layer 74 and the second inorganic particles contained in the adhesive layer 76 may be the same or different.

[0054] The average particle size (D50) of the second inorganic particles is not particularly limited and is, for example, 0.1 μm or more and 5 μm or less, preferably 0.3 μm or more and 3 μm or less, and more preferably 0.5 μm or more and 1.5 μm or less.

[0055] Here, from the viewpoint of fully exerting the effect of the second inorganic particles, the content of the second inorganic particles in the adhesive layer 76 is 3 mass% or more, preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 20 mass% or more. On the other hand, the adhesive layer 76 needs to have sufficient adhesiveness to function as an adhesive layer, and therefore the content of the second inorganic particles in the adhesive layer 76 is 65 mass% or less, preferably 60 mass% or less, more preferably 50 mass% or less, and even more preferably 40 mass% or less.

[0056] Since the adhesive layer 76 has sufficient adhesiveness to function as an adhesive layer, the electrode and the separator are bonded with sufficient strength, so that the electrode can be firmly fixed to the separator. This allows the distance between the plates (i.e., the distance between the positive electrode and the negative electrode) to be kept constant. As a result, in a non-aqueous electrolyte secondary battery, deposition of metallic lithium and retention of generated gas due to unevenness in the distance between the plates can be suppressed. Furthermore, by bonding the electrode and the separator with sufficient strength, stacking misalignment between the separator and the electrode during the manufacture of the electrode body is unlikely to occur, and the production speed of the electrode body, the yield of the electrode body, and the ease of insertion into a battery case can be improved. From the viewpoint of keeping the distance between the plates more constant, it is preferable that the adhesive layer 76 is provided on both main surfaces of the separator 70.

[0057] The adhesive layer 76 may contain only the adhesive resin and the second inorganic particles, or may further contain components other than these (in other words, other components). Examples of the other components include additives such as a defoaming agent, a surfactant, a wetting agent, a defoaming agent, and a pH adjuster.

[0058] In the illustrated example, separator 70 has only three types of layers: substrate layer 72, ceramic layer 74, and adhesive layer 76. However, separator 70 may have further layers other than substrate layer 72, ceramic layer 74, and adhesive layer 76 as long as the effects of the present invention are not significantly impaired.

[0059] The separator 70 can be manufactured according to a known method. For example, a porous resin substrate that will become the substrate layer 72 is prepared. The porous resin substrate is preferably a long substrate. A ceramic layer forming slurry containing the first inorganic particles is applied to this porous resin substrate, and dried to obtain a laminate on which the ceramic layer 74 is formed.

[0060] Next, a coating liquid containing an adhesive resin, second inorganic particles, and a solvent is prepared and applied to the laminate. At this time, the coating liquid is applied to the laminate at a predetermined pitch so as to form a stripe pattern. At this time, the coating liquid is applied along the long side of the main surface of the laminate, that is, at an angle of 20° to 70° with respect to the longitudinal direction. Such application can be performed, for example, by using a roll coater equipped with a gravure roll having grooves oblique to the rotation direction.

[0061] The applied coating liquid is dried to form the adhesive layer 76, thereby obtaining the separator 70.

[0062] The separator 70 according to the present embodiment can be used in a non-aqueous electrolyte secondary battery according to a known method. Thus, the separator 70 according to the present embodiment is typically a separator for a non-aqueous electrolyte secondary battery, and is preferably a separator for a lithium ion secondary battery.

[0063] From another viewpoint, the nonaqueous electrolyte secondary battery disclosed herein includes an electrode assembly including a positive electrode, a negative electrode, and a separator insulating these electrodes, and a nonaqueous electrolyte. The separator is the separator described above.

[0064] As an example of the configuration of the nonaqueous electrolyte secondary battery disclosed herein, a lithium ion secondary battery including the above separator will be outlined below with reference to the drawings. The lithium ion secondary battery described below is merely an example and does not limit the nonaqueous electrolyte secondary battery disclosed herein in any way.

[0065] The lithium ion secondary battery 100 shown in FIG. 4 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum.

[0066] As shown in Fig. 4 and Fig. 5, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode active material layer-free portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed) and the negative electrode active material layer-free portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer-free portion 52a and the negative electrode active material layer-free portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.

[0067] The positive electrode current collector 52 constituting the positive electrode sheet 50 may be a known positive electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.). The positive electrode current collector 52 is preferably aluminum foil.

[0068] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0069] The positive electrode active material layer 54 contains a positive electrode active material. As the positive electrode active material, a known positive electrode active material used in a lithium ion secondary battery may be used. Specifically, for example, as the positive electrode active material, a lithium composite oxide, a lithium transition metal phosphate compound, or the like may be used. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like.

[0070] The lithium composite oxide is preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element, and specific examples thereof include lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide. These positive electrode active materials may be used alone or in combination of two or more. The positive electrode active material is preferably a lithium nickel cobalt manganese composite oxide.

[0071] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.

[0072] The average particle size (median size: D50) of the positive electrode active material is not particularly limited, but is, for example, 0.05 μm or more and 25 μm or less, preferably 1 μm or more and 20 μm or less, and more preferably 3 μm or more and 15 μm or less.

[0073] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a conductive material, a binder, etc. As the conductive material, for example, carbon black such as acetylene black (AB) or other carbon materials (e.g., graphite, etc.) can be suitably used. As the binder, for example, polyvinylidene fluoride (PVDF) can be used.

[0074] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is preferably 70 mass% or more, more preferably 80 mass% to 97 mass% or less, and even more preferably 85 mass% to 96 mass% or less. The content of the trilithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably 1 mass% to 15 mass% or less, and more preferably 2 mass% to 12 mass% or less. The content of the conductive material in the positive electrode active material layer 54 is not particularly limited, but is preferably 1 mass% to 15 mass% or less, and more preferably 3 mass% to 13 mass% or less. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably 1 mass% to 15 mass% or less, and more preferably 1.5 mass% to 10 mass% or less.

[0075] The thickness of the positive electrode active material layer 54 is not particularly limited, but is, for example, from 10 μm to 300 μm, and preferably from 20 μm to 200 μm.

[0076] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be a known negative electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil is preferable as the negative electrode current collector 62.

[0077] The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined depending on the battery design. When a copper foil is used as the negative electrode current collector 62, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0078] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, soft carbon, etc. The graphite may be natural graphite or artificial graphite, or may be amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.

[0079] The average particle diameter (median diameter: D50) of the negative electrode active material is not particularly limited, but is, for example, 0.1 μm to 50 μm, preferably 1 μm to 25 μm, and more preferably 5 μm to 20 μm. The average particle diameter (D50) of the negative electrode active material can be determined, for example, by a laser diffraction scattering method.

[0080] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), etc. may be used. As the thickener, for example, carboxymethyl cellulose (CMC), etc. may be used.

[0081] The content of the negative electrode active material in the negative electrode active material layer is preferably 90% by mass or more, more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer is preferably 0.1% by mass or more and 8% by mass or less, more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer is preferably 0.3% by mass or more and 3% by mass or less, more preferably 0.5% by mass or more and 2% by mass or less.

[0082] The thickness of the negative electrode active material layer 64 is not particularly limited, but is, for example, not less than 10 μm and not more than 300 μm, and preferably not less than 20 μm and not more than 200 μm.

[0083] Separator 70 uses the separator described above, i.e., a separator in which adhesive layer 76 containing a predetermined amount of second inorganic particles is formed in a diagonal stripe pattern at a predetermined angle on at least one main surface of a laminate of substrate layer 72 and ceramic layer 74.

[0084] The nonaqueous electrolyte 80 typically contains a nonaqueous solvent and a supporting salt (electrolyte salt). As the nonaqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, and lactones that are used in electrolytes of general lithium ion secondary batteries can be used without any particular limitation. Specific examples include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such nonaqueous solvents can be used alone or in appropriate combination of two or more.

[0085] As the supporting salt, for example, a lithium salt such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0086] The nonaqueous electrolyte 80 may contain various additives other than the above-mentioned components, such as a film-forming agent such as an oxalato complex; a gas generating agent such as biphenyl (BP) or cyclohexylbenzene (CHB); a thickener, etc., as long as the effects of the present invention are not significantly impaired.

[0087] It should be noted that FIG. 4 does not strictly show the amount of nonaqueous electrolyte 80 injected into the battery case 30.

[0088] The lithium ion secondary battery 100 constructed as described above is excellent in the impregnation of the non-aqueous electrolyte into the electrode body (particularly the separator) during manufacture, and therefore has excellent production efficiency. In the lithium ion secondary battery 100, the separator 70 and the electrodes are bonded with sufficient strength, which suppresses stacking misalignment during manufacture of the electrode body 20, and also in this respect, has excellent production efficiency. The lithium ion secondary battery 100 has a small initial resistance, and an increase in resistance during repeated charging and discharging is suppressed. Furthermore, the lithium ion secondary battery 100 has a high uniformity in the distance between the electrode plates, and therefore has excellent resistance to metallic lithium precipitation.

[0089] The lithium ion secondary battery 100 can be used for various purposes. Specific applications include portable power sources for personal computers, portable electronic devices, portable terminals, etc.; power sources for driving vehicles such as electric vehicles (BEVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), etc.; and storage batteries for small power storage devices, etc., among which a power source for driving vehicles is preferable. The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of batteries are typically connected in series and / or parallel.

[0090] As an example, a rectangular lithium ion secondary battery 100 including a flat wound electrode assembly 20 has been described. However, the nonaqueous electrolyte secondary battery disclosed herein can also be configured as a lithium ion secondary battery including a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The laminated electrode assembly may include multiple separators such that one separator is interposed between each of the positive and negative electrodes, or may be one in which positive electrodes and negative electrodes are alternately laminated with one separator folded back.

[0091] The nonaqueous electrolyte secondary battery disclosed herein can also be configured as a coin-type lithium ion secondary battery, a button-type lithium ion secondary battery, a cylindrical lithium ion secondary battery, a laminated case-type lithium ion secondary battery, etc. The nonaqueous electrolyte secondary battery disclosed herein can also be configured as a nonaqueous electrolyte secondary battery other than a lithium ion secondary battery according to a known method.

[0092] Test examples relating to the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0093] <Preparation of separator for test example> A long porous polyethylene (PE) film produced by a wet process was prepared as a substrate. The thickness of this PE film was 12 μm and the porosity was 45%.

[0094] A slurry containing alumina particles with an average particle size (D50) of 0.9 μm and a binder was prepared. This slurry was applied to both sides of the above-mentioned substrate and dried to obtain a laminate in which a ceramic layer was formed on the substrate. At this time, the amount of alumina particles relative to the total solid content of the slurry was 90 mass % or more. The thickness of the formed ceramic layer was 1.5 μm per side.

[0095] A coating liquid containing polyvinylidene fluoride (PVDF), alumina particles with an average particle size (D50) of 0.9 μm, and N-methyl-2-pyrrolidone (NMP) was prepared. At this time, the amount of alumina particles relative to the total solid content of the coating liquid was the amount shown in Table 1 (when the inorganic particles were 0 mass %, the coating liquid contained only PVDF and NMP). In Test Examples 1 to 6, this coating liquid was applied in a stripe pattern on both sides of the laminate. At this time, the coating area of ​​the pattern in each test example was unified to 80%, and the width of the stripe (width of the adhesive layer) in each test example was 4 mm. In addition, the stripe angle (°) in each test example (i.e., the angle of the adhesive layer with respect to the long side of the main surface of the separator) was the angle shown in Table 1.

[0096] On the other hand, in Test Examples 7 and 8, the coating liquid was applied to the entire surfaces of both sides of the laminate. The applied coating liquid was dried to form an adhesive layer.

[0097] In each test example, the surface coverage of the adhesive layer (i.e., the ratio of the area of ​​the adhesive layer formation portion to the area of ​​the main surface of the separator) was equal to the coating area ratio of the coating liquid. In each test example, the thickness of the formed adhesive layer was 1.0 μm per side. In this manner, the separator of each test example was obtained.

[0098] <Preparation of Lithium-ion Secondary Battery for Evaluation> LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (LNCM), acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed with N-methylpyrrolidone (NMP) in a mass ratio of LNCM:AB:PVdF=87:10:3 to prepare a slurry for forming a positive electrode active material layer. This slurry was applied to an aluminum foil and dried to form a positive electrode active material layer. The obtained sheet was pressed and then cut into a width of 50 mm and a length of 230 mm to obtain a positive electrode sheet. In addition, a portion where the positive electrode active material layer was not formed was provided at the end of the longitudinal direction of the positive electrode sheet.

[0099] Graphite (C) as the negative electrode active material, styrene butadiene rubber (SBR) as the binder, and carboxymethyl cellulose (CMC) as the thickener were mixed with ion-exchanged water in a mass ratio of C:SBR:CMC=98:1:1 to prepare a slurry for forming the negative electrode active material layer. This slurry was applied to copper foil and dried to form a negative electrode active material layer. The obtained sheet was pressed and then cut to a width of 52 mm and a length of 330 mm to obtain a negative electrode sheet. In addition, a portion where the negative electrode active material layer was not formed was provided at the end of the negative electrode sheet in the longitudinal direction.

[0100] An aluminum lead was attached to the positive electrode sheet by ultrasonic welding so as to protrude in the width direction of the positive electrode sheet on the portion where the positive electrode active material layer was not formed. A nickel lead was attached to the negative electrode sheet by ultrasonic welding so as to protrude in the width direction of the negative electrode sheet on the portion where the negative electrode active material layer was not formed. The separator of each test example was cut to a size of 54 mm wide x 400 mm long. The stripe angle of the separator was the same before and after cutting.

[0101] The positive electrode sheet, the negative electrode sheet, and two separators for each test example were stacked together. The resulting laminate was wound, and the resulting wound body was pressed with a predetermined pressure to produce a flat wound electrode body. At this time, the leads of the positive electrode sheet and the leads of the negative electrode sheet were both protruding from the wound electrode body in the same direction. The outer dimensions of the wound electrode body were 41 mm x 54 mm.

[0102] An exterior body made of an aluminum laminate sheet was prepared. The obtained wound electrode body was housed in an exterior body made of an aluminum laminate sheet, and after a non-aqueous electrolyte was injected into the exterior body, the exterior body was sealed airtight. The non-aqueous electrolyte was a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3, in which LiPF6 was dissolved at a concentration of 1.1 mol / L. In this way, lithium ion secondary batteries for evaluation of each test example were obtained.

[0103] <Characteristics evaluation> [Evaluation of gas release properties] The separators for each test example were produced with a width of 3000 mm, and the separators were wound up on an 8-inch core material with a tension of 150 gf using a winding machine. If gas (i.e., air) is not released during winding of the separator, it will remain between the separator layers as air bubbles, causing unevenness in the separator layers. The appearance of the wound separator was visually observed to check for the presence or absence of unevenness caused by remaining air bubbles. The results are shown in Table 1.

[0104] [Evaluation of electrostatic charge] The separator of each test example was placed on a metal plate, and a 63 mm square weight with a load of 1.98 N was placed on top of it. Using a tensile tester equipped with a load cell, one end of the separator was pulled horizontally at a speed of 1 mm / sec, and the average friction force was measured over a distance of 50 mm after the separator began to move at a constant speed. The dynamic friction coefficient was calculated by dividing the average friction force obtained by 1.98 N. The results are shown in Table 1. The higher the electrostatic charge of the adhesive layer of the separator, the higher the dynamic friction coefficient.

[0105] [Impregnation time of non-aqueous electrolyte] Each evaluation lithium ion secondary battery into which the non-aqueous electrolyte was injected was stored in an atmosphere at a temperature of 25°C. Every hour, each evaluation lithium ion secondary battery was disassembled, and the area of ​​the portion of the separator that was not impregnated with the non-aqueous electrolyte was determined. From the relationship between time and area, the time at which impregnation of the separator with the non-aqueous electrolyte was completed was determined. The results are shown in Table 1.

[0106] [Separator Adhesion Strength Measurement] The separator of each test example was sandwiched between the positive and negative electrodes prepared above. This was then sandwiched between porous polyethylene films and further sandwiched between Teflon (registered trademark) sheets. The obtained laminate was pressed at 25°C for 10 seconds at a pressure of 60 kN. The obtained pressed product was cut into a rectangular shape of 20 mm x 120 mm to prepare a measurement sample. At this time, for the separator in which the adhesive layer was formed in a stripe shape, the longitudinal direction of the measurement sample was parallel to the direction of the stripe (i.e., the extension direction of the adhesive layer).

[0107] The measurement sample was fixed with double-sided tape onto the horizontal movable table of the tensile tester. Only the separator of the measurement sample was pulled up 90° upward (i.e., vertically) by the push-pull gauge at a speed of 200 mm / min. At this time, the movable table was moved in synchronization with the amount of movement of the push-pull gauge. The load at which the separator and the electrode peeled off was measured, and this was taken as the adhesive strength of the separator. The results are shown in Table 1.

[0108] [Battery resistance] Each evaluation lithium ion secondary battery was placed in an atmosphere at 25°C and charged to SOC 50%. Each evaluation lithium ion secondary battery was discharged for 10 seconds at a current value in the range of 0.2C to 4.0C. The voltage value after 10 seconds of discharge was plotted against each current value, and the IV resistance was calculated from the slope of the straight line obtained by linear approximation. The results are shown in Table 1.

[0109] [Table 1]

[0110] In Test Examples 1 to 6, the adhesive layer was provided on the main surface of the separator in a stripe pattern with a stripe angle of 20° to 70°. On the other hand, in Test Examples 7 and 8, the adhesive layer was provided on the entire main surface of the separator. From these comparisons, it can be seen that providing the adhesive layer on the main surface of the separator in a stripe pattern with a stripe angle of 20° to 70° increases the impregnation of the separator with the non-aqueous electrolyte, thereby reducing the battery resistance.

[0111] In addition, a comparison of Test Example 2 with Test Examples 3 to 5, and a comparison of Test Example 7 with Test Example 8, shows that the inclusion of inorganic particles in the adhesive layer improves the gas release properties of the separator and makes the separator less likely to become charged. In addition, a comparison of Test Example 4 with Test Example 8 shows that when the adhesive layer has a stripe pattern, the separator is particularly less likely to become charged. On the other hand, the results of Test Example 5 show that if the content of inorganic particles in the adhesive layer is too high, the adhesive layer does not exhibit sufficient adhesiveness.

[0112] From the above results, it can be seen that by incorporating 3% by mass or more and 65% by mass or less of inorganic particles in the adhesive layer and setting the angle between the adhesive layer and the long side of the main surface of the separator to 20° or more and 70° or less, high antistatic properties, high gas escape properties when wound, and high impregnation properties with nonaqueous electrolyte when forming the electrode assembly can be obtained. Therefore, it can be seen that the separator disclosed herein is excellent in antistatic properties, gas escape properties when wound, and impregnation properties with nonaqueous electrolyte when forming the electrode assembly.

[0113] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0114] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator 72 Base material layer 74 Ceramic Layer 76 Adhesive layer 80 Nonaqueous electrolyte 100 Lithium-ion secondary battery

Claims

1. An electrode assembly including a positive electrode, a negative electrode, and a separator that insulates the positive electrode and the negative electrode; A non-aqueous electrolyte; A non-aqueous electrolyte secondary battery comprising: The nonaqueous electrolyte secondary battery is used as a power source for driving a vehicle, The electrode body is a wound electrode body, The separator includes a substrate layer made of a porous resin, and a ceramic layer on at least one surface of the substrate layer, the ceramic layer including 85% by mass or more of first inorganic particles; The separator is elongated, The main surface of the separator has a pair of long sides, the separator further includes an adhesive layer provided on at least one of the main surfaces thereof at a predetermined pitch so as to form a stripe pattern; the adhesive layer has a portion formed as a convex portion extending in one direction from one long side to the other long side of the main surface of the separator, The adhesive layer contains an adhesive resin and second inorganic particles, The content of the second inorganic particles in the adhesive layer is 3% by mass or more and 65% by mass or less, the angle between the adhesive layer and a long side of the main surface of the separator is 20° or more and 70° or less; The width of the adhesive layer is 0.5 mm or more and 4 mm or less, and A coverage ratio of the main surface of the separator with the adhesive layer is 50% or more and 90% or less. Nonaqueous electrolyte secondary battery.

2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein an angle between the adhesive layer and a long side of the main surface of the separator is 45° or more and 60° or less.

3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the adhesive resin is polyvinylidene fluoride.

4. 4. The nonaqueous electrolyte secondary battery according to claim 1, wherein the second inorganic particles contained in the adhesive layer are particles of alumina, boehmite, magnesia, or barium sulfate.

Citation Information

Patent Citations

  • Control agent for viral disease of plant

    JP1980072101A

  • Cell and its manufacturing method

    JP2002015773A

  • Separator for power storage device

    JP2017027945A

  • Separator for secondary battery, laminate including the same, and manufacturing method thereof, wound body, secondary battery, and coating resin composition

    JP2019121507A

  • Separator for secondary battery, laminate for secondary battery, including the same, manufacturing method thereof, wound body, secondary battery, and coating resin composition

    JP2019121508A